Agro-productive assessment of Panicum maximum CV. mombasa grass in El Carmen, Manabi - Macías Loor, Diego (2019)
The objective of the research was to assess the effect of three ages (phenologies); 20, 25 and 30 days of cutting of Panicum maximum cv. Mombasa grass, on the morphology of the plant, the production of biomass (VM, DM, and% DM), Weende's proximal chemical analysis and digestibility of the fiber in neutral detergent fiber (NDF), acid detergent fiber (ADF) and lignin. The mineral profile of five elements, Ca, K, P, Mg, and Cu, constituted a useful area of 144 m2 divided into 24 experimental units with three treatments and eight repetitions. A Random Block Design was used Completely. The results were submitted to Statistical analysis on Infostat. Duncan tests were used in multiple comparisons. According to the morphological responses, Mombasa grass with a confidence interval of 95% in the number of leaves, leaf length, leaf width, plant height, and root biomass/root biomass ratio, the stem leaf ratio favored significantly at 25 days. For the variable of production, the significant difference was for the 30 days of cut. The proximal analysis shows differences at 20 days for crude protein (CP) and non-nitrogenous free extract (NNFE). The other dry matter fractions (DM) are for age at 30 days of cut. The Van Soest analysis favors the average age of the trial (25 days) and for the mineral profile, it was always significant for the 20 days of irregular cut of the Cu. The Panicum maximum cv. Mombasa at 20 days has a higher protein content, but this variety of grass responds well to cutting or grazing systems after 25 days, since between this age and 30 days the agro-productive responses showed no major differences.